2011
DOI: 10.1007/s11738-011-0749-1
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization of the Arabidopsis KS-type dehydrin protein, whose gene expression is constitutively abundant rather than stress dependent

Abstract: Dehydrins are known as plant stress-responsive genes. Arabidopsis thaliana has 10 dehydrin genes. Among them, one of the highly expressed genes is a KS-type dehydrin (At1g54410). However, the gene product, which is a histidine-rich dehydrin whose molecular mass is 11 kDa (AtHIRD11), has not been studied. Thus, we report the biochemical characterization of the AtHIRD11 protein.Although the AtHIRD11 protein was detected in all organs of Arabidopsis, the bolting stem and the flower showed higher accumulation than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 41 publications
1
37
0
Order By: Relevance
“…A recombinant AtHIRD11 protein was produced by a method reported previously (Hara et al, 2011). In brief, the open reading frame (ORF) of AtHIRD11 was inserted into the pET-30 Escherichia coli expression system (Novagen, WI, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recombinant AtHIRD11 protein was produced by a method reported previously (Hara et al, 2011). In brief, the open reading frame (ORF) of AtHIRD11 was inserted into the pET-30 Escherichia coli expression system (Novagen, WI, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Dehydrins have been detected mainly in and/or near the vasculature (Godoy et al, 1994; Danyluk et al, 1998; Bravo et al, 1999; Nylander et al, 2001, Hara et al, 2011). Studies using transgenics and mutants have reported the relationship between dehydrin expression and stress tolerance in plants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, these proteins are hydrophilic proteins that contain three conserved motifs: the K, Y, and S segments (Rorat, 2006; Eriksson et al, 2011; Hara et al, 2011). The K segment is similar in sequence to EKKGIMDKIKEKLPG, which is a common feature of all dehydrins (DHNs) and a Lys- rich motif that forms an α-helix in the C-terminus that may participate in interaction with membranes and proteins (Allagulova et al, 2003; Koag et al, 2009; Hughes et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously reported that DHN1 and DHN10 from E. globulus increase their transcript level in response to CA (Fernández et al 2012a, b). DHN10, a KS-type DHN, has been reported as a metal-binding dehydrin (Asghar et al 1994;Krüger et al 2002;Rorat 2006;Xu et al 2008;Hara et al 2011), suggesting that it can stabilize the transition metals by binding them, protecting organelles and enzymes under abiotic stress, and indirectly protecting the membrane, where the strength of ROS-reducing activities can be determined by the histidine contents (Rorat 2006) and the length of the peptides (Hara et al 2013). Keller et al (2013) reported a high representation of LEA/dehydrin in the cold transcriptome of E. gunnii, representing one of the main mechanisms of macromolecules and membrane protection, which may explain most of the hardening in this species.…”
Section: Discussionmentioning
confidence: 99%